Nonuse values of climate policy: An empirical study in Xinjiang and Beijing - Michael Ahlheim; Oliver Frör; Jiang Tong; Luo Jing; Sonna Pelz (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
Climate policy measures can be roughly subdivided into mitigation measures and adaptation measures. Mitigation policy aims at a reduction of greenhouse gas emissions with the overall goal of slowing down climate change and global warming. Since greenhouse gases like CO2, Methane etc. are global pollutants which have the same effect on world climate irrespective of where they are emitted mitigation policy creates benefits for people all over the world. Adaptation policy on the other hand does not seek to influence the world climate but, instead, is meant to reduce the negative consequences of climate change for a specific region. The benefits created by adaptation policy are, therefore, only of local importance while mitigation policy yields global benefits. This difference has, of course, consequences for the welfare economic appraisal of mitigation policy measures as compared to adaptation policy measures. Since the wellbeing of many more people worldwide is affected by mitigation measures than by adaptation measures the former will always appear more attractive in a cost-benefit analysis than the latter, at least from a global perspective. In this paper we want to show that adaption policy measures are often undervalued in cost-benefit analyses because only their so-called use values are considered, while the nonuse values they create are neglected. The use value of a commodity accrues from a direct utilization of that commodity. In an environmental context the use value of e.g. a beautiful landscape is felt by those people who visit this landscape. Beyond this use value the landscape might also have a value for people who never visit it but still enjoy the knowledge that in their country such a beautiful landscape exists and that endangered animals and plants are preserved there. This value that originates from the mere existence of a (market or environmental) good is often called its nonuse value because it is independent of a direct (and empirically observable) utilization of this good. If it can be shown that some adaptation policy measures in the context of climate policy create also nonuse values in addition to the use values this might lead to a new assessment of such measures and it might increase their chances of being approved in the political decision process. It is obvious that the systematic undervaluation of adaptation policy measures resulting from the neglect of the nonuse values they create might have the consequence that they are declined because they do not pass the cost-benefit test, though they create high nonuse values which are not considered in this test. Of course, the existence of nonuse values depends on the cultural background of the people affected by these measures and of the society they live in. Especially in an emerging country like China many people might still underestimate the importance of climate adaptation measures in comparison with economic policy measures triggering the economic growth of the country, especially if the adaptation measures are conducted in faraway regions of the country. In this study we test empirically the hypothesis that also in a growth-oriented economy like China non-materialistic values like the nonuse values of climate policy are perceived and respected by the population. This should especially hold for the better educated people living in big cities like Beijing. Therefore, we conduct a survey in Beijing where we ask people to assess a climate change adaptation project to be implemented in a faraway region, in this case in the Tarim basin in Xinjiang. In this survey we find that also Beijing citizens feel responsible for the environmental conditions in Xinjiang, especially under the impression of climate change. We find that they are even willing to contribute personally to financing a public project for the improvement of the living conditions in this remote (as viewed from Beijing) region. The rest of the paper is organized as follows: the next chapter focuses on the importance of nonuse values in environmental cost-benefit analyses; information concerning the impact of climate change on the Tarim area is provided in chapter three; the survey method and sampling procedure are introduced in chapter four; in chapter five results of the survey in Beijing are presented and analyzed, followed by some concluding remarks.
urn:nbn:de:bsz:100-opus-8277
Keywords: 330